Desert Oasis. - VILLARDI, LEOPOLDO (Architectural Record, 2026)
The article focuses on the Museo Regional de Atacama in Copiapó, Chile, a newly inaugurated state-funded museum designed by architect Max Núñez to celebrate the natural and cultural heritage of the Atacama Desert region. The three-story building, constructed with tinted concrete and extruded-clay brick, incorporates architectural elements inspired by the desert’s landscape to provide natural cooling and shading without air conditioning. The museum’s exhibitions cover the region’s geological history, Indigenous cultures, Spanish conquest, and mining industry, including the 2010 miner rescue, while temporary exhibits highlight contemporary Chilean art. Serving a community of about 168,000 residents, the museum aims to create a public space for cultural reflection and education in an otherwise isolated area.